ISOLASI DAN IDENTIFIKASI JAMUR RIZOSFER DARI TANAMAN DURIAN (Durio zibethinus Murr.) DI DESA BEMBAN, KECAMATAN SUNGAI KAKAP, PONTIANAK - Simangunsong, Ristamora; Rahmawati, Rahmawati; Mukarlina, Mukarlina (Jurnal Protobiont, 2019)
Rhizosphere fungi play an important role in the process of plant growth and development. This fungi benefits the host plant in increasing it’s growth rate, resistance to pests, diseases and drought. This study aims to determine the genus members of the durian plant rhizosphere (Durio zibethinus Murr.). Sampling of rhizosphere was carried out at Durian Plantation in Bemban Village Sungai Kakap District, Pontianak. Isolation and identification were carried out in the Microbiology Laboratory, Faculty of Mathematics and Natural Sciences, Tanjungpura University in May 2018 until December 2018. The isolation results obtained 8 rhizosphere fungi isolates.There are member of genera Aureobasidium (JRSP1), Monascus (JRSP2), Trichoderma ( JRSP3), Aspergillus (JRS4), Penicillium (JRSP5), Rhizopus (JRSP6), Aspergillus (JRSP7), Penicillium (JRSP8).